Psychosocial characteristics in children at-risk and non-risk environments - González-Arratia, Norma Ivonne (2008)
Some researchers have put in evidence the importance of the family for the individual optimal development, as well as the effects due to the lack of this. Reason why it was investigated if there are some differences between children who live in family and children who live in orphaned situation, in psychological variables such as: self-esteem, locus of control, intra-family relationships, confrontation to the problems in life, and functions of the I (self). It worked with a sample composed by 355 children of both sexes that live in family (200) and (155) who live in orphaned situation. All the children are between 9 to14 years old, and live in Toluca, Mexico State City. The results indicate differences in each one of the scales applied in favor of the family children.